Short- and Mid-term Radiographic Outcomes of Ream-then-broaching Metaphyseal Cones During Revision Total Knee Arthroplasty - Aria Darbandi, MD; Andrew Schaver, MD; Micah MacAskill, MD; Rex Lutz, DO; Amira Scaramella, BS; Christian Sangio, BS; John Shields, MD; Alvin Ong, MD; Matthew Bullock, DO MPT (Arthroplasty Today)
Background: The purpose of this study is to assess the short- and mid-term radiographic outcomes of a ream-then-broach metaphyseal cone design for revision total knee arthroplasty (rTKA). Methods: A retrospective, multicenter analysis of rTKA patients utilizing femoral and/or tibial metaphyseal cone placement from January 2017 to July 2022 was performed. Assessment of radiolucency was performed utilizing a novel “cones score” for radiolucency for tibial and femoral cones. Results: Sixty-four rTKAs (23 femoral and 59 tibial cones) with short-term follow-up (12-24 months) and 80 rTKA (24 femoral and 76 tibial cones) with mid-term follow-up (>24 months) were assessed. No intraoperative complications were reported. No cases of cone or stem aseptic loosening were observed. The cones scoring system had a significantly strong intraclass correlation between the 3 reviewers (P < .001). Of tibial cones, 96.6% and 96.1% had no change in cones scoring at short- and mid-term follow-ups, respectively. Of femoral cones, 87.0% and 100% had no change in cones scoring at short- and mid-term follow-ups, respectively. All tibial and femoral implants were deemed radiographically stable at last radiographic follow-up. Conclusions: The utilization of a ream-then-broach metaphyseal cones demonstrated excellent radiographic stability at short- and mid-term follow-ups. The use of this method has minimal risk of intraoperative or short-term failures. Surgeons should be familiar with this type of cone implantation system.